Correlates of Decentralization: Closed and Open Systems Perspectives - Negandhi, Anant R.; Reimann, Bernard C. (Academy of Management Journal, 1973)
This study examines the impact of size, technology, dependence, market condition, and organizational concern toward task environmental factors on decentralization. The results show that the degree of decentralization is influenced by the organizational concern toward task environmental factors and the degree of the firm?s dependence on other parent organizations.